TUBERCULIN RESPONSE AND SCAR FORMATION IN BCG VACCINATED 7-YEARS OLD SCHOOLCHILDREN IN SOFIA, BULGARIA - Tzvetelina Stefanova (Peytchinski Publishing, 2015)
This study has been designed to evaluate safety and efficacy of BCG vaccine in school-entering children in terms of tuberculin response to PPD and scar formation as indicators for successful vaccination. 12 BCG lots were used to immunize 1054 tuberculin-negative children at age of 7 years. Local lesions were observed and recorded 1, 3 and 12 months after immunization, and tuberculin sensitivity was measured 3 months after BCG re-immunization. The mean diameter of local reaction was 5.58±1.63 mm at 1st month, 5.13±1.56 mm at 3rd month and 4.16±1.21 mm at 12th month respectively. Tuberculin conversion was 100% and the mean diameter of induration 3 months after BCG application was 10.53±1.66 mm. All of the results obtained pointed to the fact that Bulgarian BCG vaccine induces adequate tuberculin sensitivity to a low dose of PPD tuberculin without great local skin lesions and without occurrence of any untoward vaccination reactions. Very good consistency from batch to batch is observed and this is a proof that biological activity of the Bulgarian BCG strain is kept under continuous control